2015
DOI: 10.1115/1.4029074
|View full text |Cite
|
Sign up to set email alerts
|

Application of Viscous and Iwan Modal Damping Models to Experimental Measurements From Bolted Structures

Abstract: Measurements are presented from a two-beam structure with several bolted interfaces in order to characterize the nonlinear damping introduced by the joints. The measurements (all at force levels below macroslip) reveal that each underlying mode of the structure is well approximated by a single degree-of-freedom (SDOF) system with a nonlinear mechanical joint. At low enough force levels, the measurements show dissipation that scales as the second power of the applied force, agreeing with theory for a linear vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 18 publications
(26 reference statements)
1
41
0
Order By: Relevance
“…The four-parameter Iwan model was originally developed after an extensive testing and modeling campaign [2] revealed that the Coulomb model of friction was inadequate for capturing the power-law dissipation exhibited by experimental joints. This power-law relationship continues to be observed in more recent studies [5,6,36], where Iwan models were used successfully to characterize joint behavior.…”
Section: Modelmentioning
confidence: 81%
See 4 more Smart Citations
“…The four-parameter Iwan model was originally developed after an extensive testing and modeling campaign [2] revealed that the Coulomb model of friction was inadequate for capturing the power-law dissipation exhibited by experimental joints. This power-law relationship continues to be observed in more recent studies [5,6,36], where Iwan models were used successfully to characterize joint behavior.…”
Section: Modelmentioning
confidence: 81%
“…The model carries a high degree of epistemic uncertainty due to this limitation, and ongoing research is attempting to address this shortcoming (see [52] for example). Nonetheless, since the dynamics of the structure as a whole is of modeling interest rather than the mechanics occurring in the joint, there is some confidence that the Iwan modal should capture the nonlinearity associated with at least one mode given the achievements of modal Iwan models [5,6]. As a whole-joint model composed of internal sliders, only a single Iwan element is sufficient to represent the hysteresis of the entire contact area.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations